ANALYSIS OF FISHERY COMMODITIES : THE DETERMINANT OF INDONESIA YELLOW FIN TUNA EXPORT - Aninditya Simson, Adelgar Bertranda (Jurnal Ilmiah Mahasiswa FEB, 2016)
Fishery is one of the ways to increase the Indonesia economic growth, Indonesia has a potential sector by having a huge amount of natural resources in fishery sector. Indonesia has advantage to become the homes of many biodiversity and especially become the home of yellow fin tuna. The huge amount of yellow fin tuna can become one of solutions to increase Indonesia economic growth. The demand of the yellow fin tuna all over the world is high. It is the reason Indonesia should utilize this advantage to push the export of yellow fin tuna.Analysis were performed by using panel data regression, this method is used to recognize the potential that Indonesia has on fishery sector, also to recognize the effect among the independent variables and the dependent variables. The results of the panel data regression as we know in GDP (Government Consumption), Inflation, and exchange rate have the significance impact to the total export of Indonesia yellow fin tuna performance whether it is partially and simultaneously.Keywords : Yellow fin tuna, Export Performances, Fishery sector.Â Â